A multicenter observational safety study in Swedish children and adolescents using insulin detemir for the treatment of type 1 diabetes. Issue 5 (1st March 2013) - Carlsson, Annelie; Forsander, Gun; Ludvigsson, Johnny; Larsen, Sara; Örtqvist, Eva; ,
Abstract This 26‐wk observational study in children and adolescents with type 1 diabetes (T1D) in Sweden investigated the safety and efficacy of insulin detemir (IDet) in newly diagnosed (ND) patients and those with established diabetes (ED) switching to IDet. A total of 159 patients initiated IDet as part of basal–bolus therapy, 59 in the ND stratum (mean age 9.7 yr) and 97 in the ED stratum (mean age 12.5 yr). The primary outcome measure was the incidence of severe adverse drug reactions; just one major hypoglycemic event occurred in a patient in the ND stratum during the study and one patient was withdrawn due to injection‐site reactions. All other events were classified as mild. In the ED stratum, there was a reduction in hypoglycemic events in the 4 wk prior to study end from baseline (mean reduction of 2.46 events, not significant) and a significant reduction in nocturnal hypoglycemia (mean reduction of 2.24 events, p = 0.0078). Glycemic control improved in the ND stratum as expected and, in the ED stratum, there was no significant change in HbA1c from baseline (mean reduction of −0.45%). At study end, mean daily IDet doses were 0.39 U/kg (ND) and 0.54 U/kg (ED). Weight increased by 5.7 and 2.0 kg in the ND and ED strata, respectively, and was within the normal limits for growing children. IDet provided good glycemic control and was well tolerated, with a reduced risk of nocturnal hypoglycemia in a heterogeneous cohort of children and adolescents with T1D.